2024
DOI: 10.1088/1741-2552/ad4915
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the influence of confounding factors in myoelectric control for discrete gesture recognition

Ethan Eddy,
Evan Campbell,
Scott Bateman
et al.

Abstract: Discrete myoelectric control-based gesture recognition has recently gained interest as a possible input modality for many emerging ubiquitous computing applications. Unlike the continuous control commonly employed in powered prostheses, discrete systems seek to recognize the dynamic sequences associated with gestures to generate event-based inputs. More akin to those used in general-purpose human-computer interaction, these could include, for example, a flick of the wrist to dismiss a phone call or a double ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…As described by (Saponas et al, 2008) and (Eddy et al, 2024b), the majority vote approach to discrete gesture recognition employs the legacy continuous classification approach but then converts the decision stream to a single discrete label by computing the mode of the predictions across all windows extracted from the entire gesture template. In this work, a linear discriminant analysis (LDA) classifier was used as the backbone for this majority vote approach, as it is commonly used in prosthesis control as a baseline condition for comparison (Botros et al, 2022;Duan et al, 2021).…”
Section: Majority Vote Linear Discriminant Analysis (Mvlda)mentioning
confidence: 99%
See 4 more Smart Citations
“…As described by (Saponas et al, 2008) and (Eddy et al, 2024b), the majority vote approach to discrete gesture recognition employs the legacy continuous classification approach but then converts the decision stream to a single discrete label by computing the mode of the predictions across all windows extracted from the entire gesture template. In this work, a linear discriminant analysis (LDA) classifier was used as the backbone for this majority vote approach, as it is commonly used in prosthesis control as a baseline condition for comparison (Botros et al, 2022;Duan et al, 2021).…”
Section: Majority Vote Linear Discriminant Analysis (Mvlda)mentioning
confidence: 99%
“…Similar approaches have been previously adopted in EMG-based gesture recognition, such as for hand-writing (Li et al, 2013;Huang et al, 2010) and wake-gesture recognition (Kumar et al, 2021;Eddy et al, 2024a). It has also been recently shown that DTW-based approaches can even sometimes outperform deep-learning approaches when training user-dependent models for recognizing nine discrete gestures (Eddy et al, 2024b). Using the tslearn time-series implementation of DTW distance (Tavenard et al, 2020), the 1NN DTW was adopted as a baseline for time series approaches in this work.…”
Section: Dynamic Time Warping (Dtw)mentioning
confidence: 99%
See 3 more Smart Citations